Consumption Of Health Products By Older Consumers In Peninsular Malaysia - Lee, Siew Yen (2008)

(untitled)
The purpose of the study are (i) to identify older consumers’ purchasing behavior, (ii) to determine the monthly expenditure on health products by older consumers, and (iii) to investigate factors affecting the consumption behavior of health products by older consumers in Peninsular Malaysia. The data was obtained from secondary data entitled Consumer Behavior of Older Consumers in Malaysia, funded through the Intensification of Research in Priority Areas (IRPA, Project code 06-02-03-0136-PR) by Ministry of Science, Technology and Innovation. A total of 1,356 respondents were chosen using the non-probability quota sampling. The dependent variable of this study, consumption behaviors was measured by total amount spent on health products. While, purchasing behavior was assessed by the pre-purchasing behavior, behavior during purchasing and post-purchasing behavior. Multiple linear regressions were used to identify the factors that affect the consumption behavior of health products by older consumers in Peninsular Malaysia. More than half (57.30%), of the respondents were male respondents, and that 42.70% were female respondents. There 56.19% were Malays, 29.42% Chinese, and 11.21% Indians respondents in the study, while the remaining respondents were from other ethnicities. Eight market outlets were identified where respondents had access to health products. These outlets were sundry shops, mini market, convenience store, super market, hypermarkets, pharmacies, Chinese medical halls, and traditional healers. The finding showed that 71% of the respondents (n=963) had spent less than RM114.00 per month on health products. Independent T-test showed that there were significant differences in amount of money spent on health by certain social demographic groups and that those who spent more than RM114.00 (mean) tended to be urban, female and non-working respondents (p<0.05). Pharmacies, Chinese medical halls and sundry shops are those places that the respondents normally had access to health products.There were 14 variables used in this regression model, which explained about 16% variance of monthly expenditure on health products. Of the 14 variables, eight variables significantly contributed to the model. The model showed that these eight variables were: gender, stratum, number of years education, estimated monthly household income, number of annoyances faced during purchasing, number of chronic illnesses experienced, number of prescription drugs taken, and age. Out f these eight variables number of years education and number of prescription drugs taken are the two variables that most influence respondents’ monthly expenditure on health products. In conclusion, the majority of the respondents needed health products and this need increases the cost of living for older Malaysians. In order to maintain and increase their overall quality of life, the need for a healthy lifestyle for this older population as well as for the coming generation should be addressed. Ministry of Health should provide a special scheme to help those older consumers who are receiving lower income and can not afford to purchase the health products to maintain their health. Attention must be given to proper labelling, disclosures that are easy to understand, comprehensive, accurate, and more useful in enabling consumers to understand risks and costs and to compare products. Hence, the government should fully enforce and use Labelling Acts. The Ministry of Domestic Trade and Consumer Affairs should ensure that all the market outlets follow the rules stated in the Labelling Acts.